2017
DOI: 10.1016/j.pmrj.2017.08.438
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Orthoses Use on the Changes of Foot and Ankle Joint Motions of Children With Spastic Cerebral Palsy

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Abbreviations: CES-D, Center for Epidemiological Studies-Depression; FES-I, Fall Efficacy Scale-International; VAS, Visual Analog Scale; VPT, vibration perception threshold. 8,9,33 such as balance, fear of falling, and gait, but not on actual falls. The results of within-group comparison ( Table 2 and Figure 2) suggest that participants in the IG had lower fall rate and less proportion of fallers compared to the preceding year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: CES-D, Center for Epidemiological Studies-Depression; FES-I, Fall Efficacy Scale-International; VAS, Visual Analog Scale; VPT, vibration perception threshold. 8,9,33 such as balance, fear of falling, and gait, but not on actual falls. The results of within-group comparison ( Table 2 and Figure 2) suggest that participants in the IG had lower fall rate and less proportion of fallers compared to the preceding year.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first RCT that directly assessed effects of daily use of bilateral custom‐made AFOs to reduce prospective falls in community‐dwelling older adults. A few previous studies investigated effects of AFOs on parameters related to fall risk, such as balance, fear of falling, and gait, but not on actual falls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are very few long-term studies in the literature regarding CP treatment. [30][31][32][33][34] Even current protocols, such as proposed by García-Galant et al fail to include a proper long-term assessment or follow-up. 35 Even regarding the use of invasive treatments, such as intrathecal Baclofen's or selective dorsal rhizotomy (SDR), that should actually had been better followed-up, the evidence is very scarce and insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are significant differences in kinematic parameters of the hip, knee, and ankle joints, compared to healthy children [ 14 ]. For the purpose of the improvement of the dynamic gait efficiency, different types of AFO are recommended for patients with spastic hemiplegic CP [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al evaluated the changes of foot and ankle motion in long follow-up studies (18 months) in the group of 23 children with spastic CP (7 hemiplegic, 16 diplegic), during which patients were using solid ankle–foot orthoses (SAFOs), hinged ankle–foot orthoses (HAFOs), or supramalleolar orthoses (SMO). They observed that the long term use of AFOs can lead to maintaining or improving foot and ankle motion and function [ 15 ]. In our study, the step length was longer while the subjects were walking with AFO, comparing to walking barefoot, the gait speed has also improved significantly and the gait cadence was reduced.…”
Section: Discussionmentioning
confidence: 99%